Predatory journals: an enemy to be fought in scientific communication - Guimarães, José Augusto C. [UNESP]; Hayashi, Maria Cristina P.I. (Universidade Estadual de Campinas, 2023)
Introduction: Scientific production is a fundamental element for the reputation of a researcher and a university in such a way that the pressure to publish becomes increasingly prevalent in academia. Objective: We seek to analyze the growing phenomenon of predatory journals as a threat to the scientific universe and the ways in which they can be identified and avoided. Methodology: Based on the international literature, the concept, characteristics and ways of identifying predatory journals are discussed, in addition to some questions that can illuminate reflections on the ethical impacts that this reality has brought to the academic environment. Results: It is evident the need to face this threat through a joint action of authors (researchers), editors, teaching and research institutions, research funding agencies, and bibliographic databases in order to guarantee that scientific communication in the most diverse fields of knowledge is carried out in ethical, transparent and defensible ways. Conclusion: It is necessary for investigators to develop a specific competence to distinguish between reliable and fraudulent journals, disregarding invitations, which are often tempting, to publish or join editorial committees of predatory journals.
Revistas predatórias: um inimigo a ser combatido na comunicação científica
Keywords: Information ethics; Predatory journals; Scientific communication; Scientific journals